Differential regulation of aldose reductase expression during macrophage polarization depends on hyperglycemia: $hChristian Erbel, Gregor Rupp, Gabriele Domschke, Fabian Linden, Mohammadreza Akhavanpoor, Andreas O. Doesch, Hugo A. Katus, Christian A. Gleissner - Erbel, Christian; Rupp, Gregor Fabian; Domschke, Gabriele; Linden, Fabian; Akhavanpoor, Mohammadreza; Dösch, Andreas; Katus, Hugo; Gleißner, Christian A. (Innate immunity, 2016)
Aldose reductase (AR; gene AKR1B1) is the rate-limiting enzyme of the polyol pathway and has been associated with diabetes and atherosclerosis. Here, we sought ...